The effect of subconjunctival bevacizumab on angiogenesis in rabbit model - Nurwasis, Nurwasis (The Center For Medical Science Community Faculty of Medicine Universitas Airlangga, 2019)
The wound healing process is major cause of glaucoma surgery failure and enhances the incapability of controlling the IOP. This aim of study was to evaluate the angiogenesis effect of Bevacizumab injection on the amount and density of blood vessels in the rabbit model after trabeculectomy. It was a true experimental study using 16 eyes of 16 New Zealand White Rabbit (Oryctolagus cuniculus) that divided into two groups. The control group was treated with 0.05 ml of Balanced Saline Solution (BSS). The experimental group was treated with subconjunctival injection of 1.25 mg Bevacizumab in 0.05 BSS. All rabbit was sacrificed, and the eye was enucleated. Thus, the bleb area was dissected after 14 days. Histopathological analysis was performed to evaluate the amount and density of blood vessels. The mean amount of blood vessels in the control group was 22.63 ± 11.02, and the experimental group was 14,75 ± 4.92 (p=0.043). The mean of blood vessel density in the control group was 19.10 ± 1.69 %, and the experimental group was 16.53 ± 2.90 % (p=0.029)%. There was a statistically significant difference between the two groups (p<0.05). Subconjunctival bevacizumab in the rabbit model reduces the amount and density of blood vessels compared with subconjunctival BSS injection.